Anterior cingulate cortex: A brain system necessary for learning to reward others? - Lockwood, PL; O’Nell, KC; Apps, MAJ (Public Library of Science, 2020)
Helping a friend move house, donating to charity, volunteering assistance during a crisis. Humans and other species alike regularly undertake prosocial behaviors—actions that benefit others without necessarily helping ourselves. But how does the brain learn what acts are prosocial? Basile and colleagues show that removal of the anterior cingulate cortex (ACC) prevents monkeys from learning what actions are prosocial but does not stop them carrying out previously learned prosocial behaviors. This highlights that the ability to learn what actions are prosocial and choosing to perform helpful acts may be distinct cognitive processes, with only the former depending on ACC.